Influence of bed material density on local scour around spur dikes - Couto, L. T. (2015)
An experimental study on local scour has recently started in a laboratory flume at the National Laboratory of Civil Engineering (LNEC) in Lisbon. The main objective of this study is the investigation of the influence of the sediment specific density on the final scour hole around a spill-through spur dike placed perpendicular to the flow, in order to improve knowledge for the use of light-weight bed materiaIs in physical modelling. The results of three sets of runs under regime conditions, corresponding to two different mixtures of river sand and a light weight bed material, are discussed. Experiments were made under live-bed and with clear-water conditions, for which different equations, obtained by multiple regression ana1ysis, are suggested, allowing the prediction of the maximum scour depth. The paper presents the results already obtained and the discussion on maximum scour depth and geometric characterisation of the scour holes in the framework of existing literature.